2023
DOI: 10.3389/fpsyg.2023.1294026
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of mental health of university students in Hong Kong under COVID-19

Daniel T. L. Shek,
Wenyu Chai,
Diya Dou
et al.

Abstract: Although the COVID-19 pandemic has caused many problems for university students, there are several research gaps in the study of psychological well-being of Hong Kong university students. First, few studies have examined different ecological correlates of mental health in a single study. Second, few studies have used both psychological morbidity and positive well-being as indicators of mental health. Third, we know little about the relationships between university students’ perceived need satisfaction, difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
(173 reference statements)
0
2
0
Order By: Relevance
“…Rapid changes in education were inevitable owing to changes in clinical settings and the impact of the repeated outbreaks (20). Further efforts are required to prevent adverse mental health outcomes and reduce the prevalence of mental health problems (21). Clinical nurses' negative psychology positively impacted burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid changes in education were inevitable owing to changes in clinical settings and the impact of the repeated outbreaks (20). Further efforts are required to prevent adverse mental health outcomes and reduce the prevalence of mental health problems (21). Clinical nurses' negative psychology positively impacted burnout.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Savage et al (2020) showed that students’ mental well-being deteriorated during the lockdown period. Shek et al (in press) have also summarized the findings on the deteriorating student mental health profiles in the early days of the pandemic. In the present study, we attempted to examine the mental health and related sociodemographic as well as psychosocial predictors in Chinese university students in Hong Kong under the pandemic.…”
Section: Introductionmentioning
confidence: 99%